The importance of foreign language in the application of specific foreign trade terminologies - Vieira, Gabriel Calegario (2020)
A subject that is growing and has become part of people's lives, foreign languages, was something that few people had before, and it was even considered as a differential. But today, it is already part of everyday’s life for Brazilians, even if not everyone has a second language in their curricula. this directly influences international trade, where a second language, preferably English, is a minimum requirement to have understanding among the nations. When it comes to foreign trade, there are many specific terms that apply to the area and can generally only be understood by market players. The purpose of this research is to show the present relationship between languages and the terminologies of world trade, as well as to present such terms.